Postmemory, stereotype, and the return home. Rewriting pre-existing narratives in Sofi Oksanen’s "Purge" - Mrozewicz, Anna Estera (Folia Scandinavica Posnaniensia, 2016)
The article offers a discussion of Sofi Oksanen’s novel Purge, focusing on the book’s strategy of evoking stereotypical narratives about Eastern Europe, such as the (postcommunist) fallen woman and (Russian) return home narratives, as well as related intertexts, primarily Lukas Moodysson’s film Lilya 4-ever. I argue that Oksanen constructs the plot around clichés in order to challenge them in a subversive fashion, first and foremost, in the name of recuperating the notion of Home. Related to locality and the feeling of being at-home, where the wholeness of the (national) subject is possible, ‘home’ is staged as an alternative to stereotypes, associated with transnational travel and the apparatus of colonization. A significant counter-narrative embedded in the novel – and hitherto rarely discussed – is the exilic perspective with its idealization of the lost and imagined home(land). In Purge, this is mediated through the main character’s postmemory. By means of a postexilic narrative, home is reconfigured as a ‘third space’ – neither fully ideal and (ethnically) pure nor adhering to the aforementioned stereotypical narratives. The positive valorisation of home, despised by some critics as simplistic and conservative, does not prevent movement and dislocation from being included in the new experience of home(land) emerging from the post-Soviet condition.